Northwest history. Mining. Products. Zinc. 1937-05-02 (1937)
One-time lowly zinc to front. - Lawn mowers, sewing machines and radios being made of metal. - More is being heard these days of the growing uses of zinc than of any other metal, a remarkable change from not so many years ago when the presence of zinc in ore penalized the shipper and made the metal a cause for worry for the mine owner.